Effects of Personality Traits on Service Provision of librarians in University Libraries in Kwara State, Nigeria - LAARO, MEDINAT DOLAPO; OPELE, JACOB KEHINDE (MiddleBelt Journal of Library and Information Science, 2020)
Among the many functions of the university are the provision of quality education, facilities for education and development of knowledge and their application to government, industry, commerce and the community. However, the extent to which librarians provide these services in universities in Kwara State, Nigeria, is unknown. The significance of people’s personality characteristic in information service provision in any university library cannot be neglected. This study examined the influence of personality traits on information service provision of librarians in university libraries in Kwara State. It employed the survey research design with study population 78 academic librarians in four university libraries and 68,298 undergraduates. Proportionate sampling technique was used to select 382 undergraduate students and total enumeration for academic librarians. Data were collected using two sets of questionnaires. The reliability test of the questionnaires yielded the following Cronbach’s Alpha co-efficient: level of service provision = 0.77 and personality trait = 0.76. Data were analysed using descriptive and inferential statistics. Frequency counts and percentage distribution, mean and standard deviation were generated for all the research questions while simple regression analysis was used to test the hypothesis formulated. The findings revealed that information services were provided by librarians almost every time to library users. Lending and library loan (M = 4.2), reference services (M = 4.2), user education (M = 4.1) and shelf management/arrangement (M = 4.1) were frequently provided services. Openness (M = 3.96) was the most influencing traits in terms of mean score when compared with other traits; extraversion (M= 3.52), neuroticism (M= 3.47), agreeableness (M = 3.52) and conscientiousness (M = 3.13). Personality traits significantly influenced information service provision (Adj R = .044, F (1, 76) = 4.518, P =.037). The study concluded that the students perceived the information services provided by librarians as satisfactory. It was recommended that the current level of service provision should be maintained to enhance more patronage to the library. The five personality traits; extraversion, neuroticism, agreeableness, conscientiousness and openness of librarians should be regularly appraised for a sustained information service provision in these libraries.